Pengaruh Digital Marketing, Brand Awareness dan Brand Image Terhadap Keputusan Pembelian Produk Moisturizer Pada Skincare Skintific (Studi Pada Mahasiswi Universitas Islam Malang Angkatan 2021) - Putri, Devina Anggraini; Djaelani, Abdul Kodir; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine and analyze the relationship between the influence of digital marketing, brand awareness and brand image on purchasing decisions on skintific skincare. This study uses a case study on Unisma students where data is obtained by distributing questionnaires via g-form to Unisma students selected by purposive sampling. Determination of the number of samples in this study using the Slovin formula and the results obtained were 96 respondents. The analysis methods used in this study are instrument testing, (validity testing, reliability testing), normality testing, classical assumption testing (multicollinearity testing, heteroscedasticity testing), multiple linear regression analysis, hypothesis testing (F test and t test), determination coefficient testing (Adjusted R2) data processing using the IBM SPSS 26 program. The results of this study indicate that the influence of digital marketing, brand awareness, brand image simultaneously influences purchasing decisions. Digital Marketing partially influences purchasing decisions, Brand Awareness partially influences purchasing decisions, Brand Image partially influences purchasing decisions. Keywords: Digital Marketing, Brand Awareness, Brand Image, Keputusan Pembelian